Design of Identification System for Red and White Meranti Using Colours Detection Method - Firmansyah Burlian (Universitas Sriwijaya, 2016)
Development technology of computer programs caused to produce novelty from the development of these technologies. Besides to education, the development of technology can be utilized in working, even all. Digital image processing is a part the development of it. This research develop of identification system of red and white meranti by using color detection method. The program used in this research is a Matlab program. In this research, database made by 25 pieces red meranti and 25 pieces white meranti. Image of woods captured side by side using webcams. Then taking the values of primary colors RGB (red, green, blue) to be used as database. Identification system will test 5 times for every red and white meranti with different positions. Success rate of identification system red and white meranti using color detection method is 90.83%.